2004
DOI: 10.1007/s00442-004-1602-7
|View full text |Cite
|
Sign up to set email alerts
|

Fly parasitoid Megaselia opacicornis uses defensive secretions of the leaf beetle Chrysomela lapponica to locate its host

Abstract: Larvae of the leaf beetle Chrysomela lapponica derive a defensive secretion from salicyl glucosides found in the host plant Salix borealis. This secretion protects beetle larvae from some natural enemies, but does not appear to repel parasitoids. We tested the hypothesis that the fly parasitoid Megaselia opacicornis (Diptera, Phoridae) uses the larval defensive secretion of Ch. lapponica in its search for prey. In the field, nearly 30 times more M. opacicornis individuals were caught on leaves coated with stic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Host plant-derived salicylaldehyde appeared not to be effective against some generalist predators, such as predatory bugs (Rank et al, 1998) or wasps (Pasteels & Gregoire, 1984;Sears et al, 2001), but has been proven to attract specialist predators and parasitoids (Rank, Smiley & K€ opf, 1996;Gross et al, 2004;Zvereva & Rank, 2004;von Fragstein et al, 2013). Consistently, meta-analysis showed non-significant overall effectiveness of salicylaldehyde-containing secretions across several prey and enemy species (Zvereva & Kozlov, 2016).…”
Section: Do Leaf Beetles Obtain Enemy-free Space Onmentioning
confidence: 63%
“…Host plant-derived salicylaldehyde appeared not to be effective against some generalist predators, such as predatory bugs (Rank et al, 1998) or wasps (Pasteels & Gregoire, 1984;Sears et al, 2001), but has been proven to attract specialist predators and parasitoids (Rank, Smiley & K€ opf, 1996;Gross et al, 2004;Zvereva & Rank, 2004;von Fragstein et al, 2013). Consistently, meta-analysis showed non-significant overall effectiveness of salicylaldehyde-containing secretions across several prey and enemy species (Zvereva & Kozlov, 2016).…”
Section: Do Leaf Beetles Obtain Enemy-free Space Onmentioning
confidence: 63%
“…Three main possible selection factors have been investigated so far: (1) the inXuence of abiotic factors like irradiation and temperature (Gross et al 2004c), (2) bottom-up eVects which inXuence the performance of the beetles directly, like the diVerent host plants (Gross et al 2004a;Zvereva and Rank 2003), or indirect bottom up eVects inXuencing the larval defensive abilities (Gross et al 2002;Pasteels et al 1983;Schulz et al 1997), and (3) top down eVects by predators, parasitoids and entomopathogens (Gross et al 2004b;Zvereva and Rank 2004). Further, crossing experiments were conducted, showing reproductive isolation between the birch and willow-specialised populations of C. lapponica (Fatouros et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Chrysomela knabi may choose a suboptimal host plant because the larvae grown on S. eriocephala would be less attractive to natural enemies that specialize on larvae grown on S. sericea. As previously stated, natural enemies have been noted to exploit larval defence as signals to locate their prey ( Köpf et al , 1998;Rank et al , 1998;Zvereva & Rank, 2004 ). Avoidance of intraspecific competition may also favour oviposition on suboptimal plants ( Craig et al , 1990 ).…”
Section: Figurementioning
confidence: 91%
“…Zvereva and Rank (2004) found that the fly parasitoid Megaselia opacicornis uses the larval defensive secretions of the leaf beetle Chrysomela lapponica as a host finding cue. Thus, C. lapponica experience higher mortality by M. opacicornis when they have a greater concentration of defensive secretions.…”
Section: Figurementioning
confidence: 99%